Energy expenditure during tennis play: A preliminary video analysis and metabolic model approach - Botton, F.; Hautier, C.; Eclache, J.-P. (The Journal of Strength and Conditioning Research, 2011)
The aim of this study was to estimate, using video analysis, what proportion of the total energy expenditure during a tennis match is accounted for by aerobic and anaerobic metabolism, respectively. The method proposed involved estimating the metabolic power (MP) of 5 activities, which are inherent to tennis: walking, running, hitting the ball, serving, and sitting down to rest. The energy expenditure concerned was calculated by sequencing the activity by video analysis. A bioenergetic model calculated the aerobic energy expenditure (EEO2mod) in terms of MP, and the anaerobic energy expenditure was calculated by subtracting this (MP - EEO2mod). Eight tennis players took part in the experiment as subjects (mean ± SD: age 25.2 ± 1.9 years, weight 79.3 ± 10.8 kg, VO2max 54.4 ± 5.1 ml/kg/min). The players started off by participating in 2 games while wearing the K4b2, with their activity profile measured by the video analysis system, and then by playing a set without equipment but with video analysis. There was no significant difference between calculated and measured oxygen consumptions over the 16 games (p = 0.763), and these data were strongly related (r = 0.93, p < 0.0001). The EEO2mod was quite weak over all the games (49.4 ± 4.8% [latin capital V with dot above]O2max), whereas the MP during points was up to 2 or 3 times the VO2max. Anaerobic metabolism reached 32% of the total energy expenditure across all the games 67% for points and 95% for hitting the ball. This method provided a good estimation of aerobic energy expenditure and made it possible to calculate the anaerobic energy expenditure. This could make it possible to estimate the metabolic intensity of training sessions and matches using video analysis.